Cody

# Problem 233. Reverse the vector

Solution 2007975

Submitted on 7 Nov 2019 by Domenico Galati
This solution is locked. To view this solution, you need to provide a solution of the same size or smaller.

### Test Suite

Test Status Code Input and Output
1   Pass
x = 1; y_correct = 1; assert(isequal(reverseVector(x),y_correct))

n = 1

2   Pass
x = -10:1; y_correct = 1:-1:-10; assert(isequal(reverseVector(x),y_correct))

n = 12 y = 1 0 0 0 0 0 0 0 0 0 0 -10 y = 1 0 -1 0 0 0 0 0 0 0 0 -10 y = 1 0 -1 -2 0 0 0 0 0 0 0 -10 y = 1 0 -1 -2 -3 0 0 0 0 0 0 -10 y = 1 0 -1 -2 -3 -4 0 0 0 0 0 -10 y = 1 0 -1 -2 -3 -4 -5 0 0 0 0 -10 y = 1 0 -1 -2 -3 -4 -5 -6 0 0 0 -10 y = 1 0 -1 -2 -3 -4 -5 -6 -7 0 0 -10 y = 1 0 -1 -2 -3 -4 -5 -6 -7 -8 0 -10 y = 1 0 -1 -2 -3 -4 -5 -6 -7 -8 -9 -10

3   Pass
x = 'able was i ere i saw elba'; y_correct = 'able was i ere i saw elba'; assert(isequal(reverseVector(x),y_correct))

n = 25 y = 97 98 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 0 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 0 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 0 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 0 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 0 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 0 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 0 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 0 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 0 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 0 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 0 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 119 0 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 119 32 0 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 119 32 101 0 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 119 32 101 108 0 97 y = 97 98 108 101 32 119 97 115 32 105 32 101 114 101 32 105 32 115 97 119 32 101 108 98 97